Upaya Guru Dalam Mengatasi Kesulitan Siswa Dalam Berhitung Dengan Menggunakan Media Angka di Kelas II SD Negeri 1501 Hurung Jilok - Emma Salama Hasibuan; Mira Yanti Lubis; Hopman Daulay (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The purpose of this research is to determine (1) Difficulty in calculating in class II of SD Negeri 1501 Hurung Jilok. (2) The teacher's efforts to overcome students' difficulties in calculating using number media in class II of SD Negeri 1501 Hurung Jilok. The type of research used is Classroom Action Research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. This research was carried out in class II of SD Negeri 1501 Hurung Jilok. The data sources in this research were divided into two, namely (1) primary data, namely students of class II of SD Negeri 1501 Hurung Jilok, (2) secondary data, namely teachers of class II of SD Negeri 1501 Hurung Jilok. . Data collection techniques in this research were obtained through observation, oral tests and documentation. The data analysis technique in this research is a qualitative data analysis technique. Based on the results of the research carried out by the author, conclusions can be put forward: (1) The difficulty in calculating in class II of SD Negeri 1501 Hurung Jilok based on the results of observations of the level of difficulty in calculating in the pre-cycle stage, there were 13 students experiencing difficulties in learning arithmetic, while 14 students did not have difficulty learning arithmetic. Based on the results of these observations, researchers want to overcome students' difficulties in calculating using number media in class II of SD Negeri 1501 Hurung Jilok. Because by using number media, learning will be more fun so that students will find it easier to overcome counting difficulties. (2) The teacher's efforts to overcome students' difficulties in arithmetic using number media in class II of SD Negeri 1501 Hurung Jilok have been resolved, because with each action taken, students' arithmetic difficulties begin to decrease gradually, as in cycle I, students' difficulties in arithmetic using using number media in class II of SD Negeri 1501 Hurung Jilok experienced a decline, namely the remaining 6 students or 22.22% who experienced difficulties in learning arithmetic, while 21 students or 77.78% had no difficulty in learning arithmetic, and in cycle II students had difficulty in learning arithmetic. arithmetic using number media in class II of SD Negeri 1501 Hurung Jilok cycle II experienced a decrease from the previous cycle, namely there was 1 student or 3.70% who had difficulty learning to count, while 26 students or 96.30% had no more difficulty in learning counting. So it can be concluded that by using number media, the numeracy difficulties of class II students at SD Negeri 1501 Hurung Jilok can be overcome.